2017
DOI: 10.1097/md.0000000000007664
|View full text |Cite
|
Sign up to set email alerts
|

Successful ceftazidime-avibactam treatment of MDR-KPC-positive Klebsiella pneumoniae infection in a patient with traumatic brain injury

Abstract: Rationale:Carbapenem-resistant Enterobacteriaceae infections are a serious health care problem, because of the high mortality. Carbapenem resistance is mainly caused by carbapenemases production, including Klebsiella pneumoniae carbapenemase (KPC). Ceftazidime-avibactam is a new cephalosporin/β-lactamase inhibitor combination for the treatment of complicated urinary, intra-abdominal infections, and nosocomial pneumonia caused by gram negative, or other serious gram-negative infections.Patient concerns:We showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Laurent adopted a combined pharmacotherapy regimen of dual carbapenems to provide a new approach in the treatment of CRE-induced infections [ 31 ]. As a novel β-lactam/β-lactamase inhibitor, studies have shown that ceftazidime-avibactam can successfully cure the infections due to Enterobacteriaceae with bla KPC [ 32 – 35 ]. Nevertheless, it is worth to be noticed that with the increasing application of ceftazidime-avibactam, the resistant strains and failed cases have been reported [ 6 , 7 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laurent adopted a combined pharmacotherapy regimen of dual carbapenems to provide a new approach in the treatment of CRE-induced infections [ 31 ]. As a novel β-lactam/β-lactamase inhibitor, studies have shown that ceftazidime-avibactam can successfully cure the infections due to Enterobacteriaceae with bla KPC [ 32 – 35 ]. Nevertheless, it is worth to be noticed that with the increasing application of ceftazidime-avibactam, the resistant strains and failed cases have been reported [ 6 , 7 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the in vivo clinical efficacy of ceftazidime-avibactam has been widely demonstrated [ 12 , 13 ], several studies have recently reported in K. pneumoniae epidemic clones the emergence of new ceftazidime-avibactam resistant KPC enzymes derived from point mutations in bla KPC-2 and bla KPC-3 genes, frequently after the antibiotic exposure [ 16 , 17 , 18 ]. In all cases, in vitro meropenem susceptibility was fully or partially restored due to these bla KPC mutations resulting in KPC-producing K. pneumoniae isolates with a phenotype resembling that of ESBL producers [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In February 2015, the U.S. Food and Drug Administration (FDA) approved the ceftazidime-avibactam combination as an alternative to carbapenems in patients with complicated intra-abdominal and urinary tract infections caused by MDR Gram-negative bacteria isolates [ 11 ]. Since then, several studies have demonstrated the in vivo efficacy of ceftazidime-avibactam in the treatment of infections caused by KPC-producers [ 12 , 13 , 14 ]. Moreover, a recent study has supported the presumptive use of ceftazidime-avibactam against carbapenem resistance E. coli isolates, including members of the ST131 lineage [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies support the in vivo efficacy of ceftazidime-avibactam against ceftazidime-resistant isolates, with one study showing it to be superior to best available therapy (BAT), mostly carbapenems, in UTIs caused by these organisms [73•]. There are limited but growing clinical data illustrating ceftazidime-avibactam efficacy in treating infections in humans caused by KPC-producing pathogens [74][75][76].…”
Section: Ceftazidime-avibactammentioning
confidence: 99%